Poor artists - Puente, Gabrielle de la 1994-; Muhammad, Zarina 1982- (Particular Books, 2024)
Why make art? Faced with a capitalist system that has turned art into artwork and creative expression into cut-throat competition, why do so many artists try anyway? In this eye-opening journey through the bizarre world of contemporary art, criticism duo The White Pube tell the story of art like never before. Poor Artists follows aspiring artist Quest Talukdar through childhood obsessions, art school lessons and her professional debut. In surreal encounters with other artists, Quest learns profound truths about money and power, and must decide whether she cares more about success or staying true to herself. Blending imaginative storytelling with dialogue from anonymized interviews with real people in the art world who have all had to wrestle with the same decisions – including a Turner Prize winner or two, a few ghosts, a Venice Biennale fraudster and a communist messiah – Poor Artists is a powerful testimony to the emotional, existential and financial experience of artists today.
Keywords: Kritik; Kunstbetrieb; Arbeitsbedingungen